Hydrotreatment of pyrolysis bio-oil: A review - Han, Yinglei; Gholizadeh, Mortaza; Tran, Chi-Cong; Kaliaguine, Serge; Li, Chun-Zhu; Olarte, Mariefel; Garcia-Perez, Manuel (Fuel processing technology, 2019)
Fast pyrolysis converts >60 wt% of lignocellulosic materials into bio-oil. The two-step bio-oil hydrotreatment concept has had a major impact in the development of bio-oil hydro-treatment. In the first step, known as stabilization, the carbonyl and carboxyl functional groups are transformed into alcohols between 373 and 573 K, in the presence of noble metals (Pt, Ru and Pd) supported on carbon and metal oxides. In the second step, between 623 and 673 K, cracking and hydro-deoxygenation occur using Ru, Ni or sulfided CoMo catalysts. Transition metal phosphides and carbides are also active. The first section is devoted to summarizing the current understanding of bio-oil composition. The second section is an overview of bio-oil hydrotreatment processing parameters. Many of the bio-oil hydrotreatment studies in the literature are based on model compound results, which are reviewed in the third section. Section four is devoted to review studies with bio-oil fractions and the nature of polymerization and cross linked reactions responsible for catalyst deactivation. The progress in the development of new catalysts is discussed in section five. The review ends with a discussion on future prospects and challenges to hydrotreat pyrolysis bio-oils. •The two steps hydrotreatment concept had a major impact in the development of the field•Most common catalysts used in stabilization step: Pt, Ru and Pd•Most common catalysts for de-oxygenation: Ru, Ni and sulfided CoMo•Separation of bio-oil into fractions and separate processing is necessary•HDO of oligomeric fractions is challenging